Evaluation of Spermicidal and Antimicrobial Activities of Methanolic Extract of Leucas aspera and Structural Elucidation of Separated Active Component - De, Biplab; Chakraborty, Avijit; Majumder, Tandrima; Chanda, Shilpi; Behari Goswami, Binoy (Asian Journal of Chemistry, 2010)
The methanolic extract of whole plant of Leucas aspera was evaluated for its spermicidal and antimicrobial activity. Total four compounds were separated from the extract by column chromatography and the same activities were evaluated for the separated compounds also. The structure of highest active component was elucidated.